2019
DOI: 10.1007/s00464-019-06742-w
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopy in prone position with two-lung ventilation compared to conventional thoracotomy during Ivor Lewis procedure: a multicenter case–control study

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Our results are also consistent with those presented by Souche et al. ( 9 ), in which the major postoperative pulmonary complications were significantly lower in the minimally invasive oesophagectomy group compared with a hybrid surgery group. However, we had a sample size of approximately twice as many patients.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are also consistent with those presented by Souche et al. ( 9 ), in which the major postoperative pulmonary complications were significantly lower in the minimally invasive oesophagectomy group compared with a hybrid surgery group. However, we had a sample size of approximately twice as many patients.…”
Section: Discussionsupporting
confidence: 93%
“…In the unmatched dataset, we found that TILO was associated with less postoperative pneumonia (15.2 vs 25.0%; P = 0.038), and pleural effusion (4.3 vs 14.1%; P = 0.005) than the HILO group ( Table 2 ). Furthermore, TILO was associated with shorter chest drainage than the HILO group (median(IQR) 8 ( 6 9 ) vs 8 (7–10.5) days; P = 0.003). The anastomotic leak rates were not significantly different between TILO and HILO (7.2% vs 6.4%, P = 0.772).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…To date, no randomized trial has compared the hybrid laparoscopic route to the totally minimally invasive route. Indeed, several retrospective studies have shown an increase in the rate of anastomotic fistula in the thoracoscopy group [ 21 ]. A precise study of the advantage of the thoracoscopic route and a reliable and reproducible technique are essential.…”
Section: Surgical Trendsmentioning
confidence: 99%
“…Management of anastomotic leaks after esophagectomy and gastric pull-up (MIE) being the most common (1). Other less frequently performed operations such as prone esophagectomy with two-lung ventilation and mediastinoscopic esophagectomies also have been described in the literature (2,3). Regardless of surgical approach, esophagectomy is associated with high overall morbidity and significant mortality rates.…”
Section: Review Articlementioning
confidence: 99%